2019
DOI: 10.36341/jops.v2i1.1015
|View full text |Cite
|
Sign up to set email alerts
|

PENETAPAN KADAR VITAMIN C DENGAN SPEKTROFOTOMETRI UV-Vis PADA BERBAGAI VARIASI BUAH TOMAT

Abstract: Tomato is a kind of fruit containing vitamin C. Vitamin C is needed for collagen production, bone and teeth formation, wound healing, and immunity to infection. This vitamin is dissolve in water and easy to be destroyed by light and high temperature, so the storage and condition of tomato fruits need special attention to keep an adequate vitamin C level it contained. This research aimed to determine the level of vitamin C in three kinds tomato fruits maturation degree: raw, half-mature, and mature. The quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
3
0
12
Order By: Relevance
“…After obtaining the ascorbic acid regression equation, amounts of vitamin C in infused water would be determined. The derived linear regression equation, has an r-value of 0.9956, the correlation coefficient, is y = 0.07807x + 0.01844 Very good linearity is indicated by A correlation coefficient (r) of greater than 0.99 and acceptance criterion [8] (Dewi, 2019). The results showed that elephant ginger infused water with a 12-h soak duration had the highest levels of vitamin C in infused water at 72.44 ppm, and elephant ginger-infused water with a 6-h soaking time had the lowest levels at 52.7 ppm.…”
Section: Vitamin C Levels In Infused Watermentioning
confidence: 99%
See 1 more Smart Citation
“…After obtaining the ascorbic acid regression equation, amounts of vitamin C in infused water would be determined. The derived linear regression equation, has an r-value of 0.9956, the correlation coefficient, is y = 0.07807x + 0.01844 Very good linearity is indicated by A correlation coefficient (r) of greater than 0.99 and acceptance criterion [8] (Dewi, 2019). The results showed that elephant ginger infused water with a 12-h soak duration had the highest levels of vitamin C in infused water at 72.44 ppm, and elephant ginger-infused water with a 6-h soaking time had the lowest levels at 52.7 ppm.…”
Section: Vitamin C Levels In Infused Watermentioning
confidence: 99%
“…Vitamins are organic compounds that, even in small amounts, are needed by the human body to maintain life and health. A vital coenzyme or cofactor in the organism, Water-soluble vitamins include vitamin C that helps to speed up metabolic processes [8,11].…”
Section: Vitamin C Levels In Infused Watermentioning
confidence: 99%
“…Spektrofotometri UV-Vis merupakan instrumen yang digunakan untuk menentukan konsentrasi senyawa berdasarkan kemampuan senyawa tersebut untuk menyerap radiasi cahaya dengan panjang gelombang tertentu dalam rentang 200-400 nm, yang menghasilkan cahaya monokromatik (Dewi, 2018). Panjang gelombang maksimum ditentukan untuk mengukur daerah serapan maksimum larutan standar serta larutan sampel berupa nilai absorbansi maksimum (Lidyawati et al, 2020).…”
Section: Spektrofotometri Uv-visunclassified
“…Baku pembanding vitamin C ditimbang sebanyak 0,05 g (50 mg), kemudian dimasukkan ke dalam labu ukur 500 mL yang telah dibungkus alumunium foil dan ditambahkan dengan akuades sampai tanda batas, kemudian dihomogenkan. Didapat larutan vitamin C dengan konsentrasi 100 ppm (Dewi, 2019).…”
Section: Analisis Kuantitatif a Pembuatan Larutan Induk Vitamin C 100...unclassified